THE IMPROVEMENT OF SERVICE QUALITY TOWARD SALES OF TICKETS AND MEMBERSHIP OF GARUDA INDONESIA AIRLINE FOR ENHANCING ASEAN ECONOMIC COMMUNITY - Dotulong, Lucky O. H. (Journal of Asean Studies on Maritime Issues, 2016)
In the new competition era of Asean Economics Community (ASC), transportation has become one of the most important services for supporting people‟s daily activities. Therefore, Garuda Indonesia as one of airline in Indonesia should be focus on service quality. In order to maximize the service performance, Garuda gives full of service by providing facilities such as lobby lounge and member cards (GarudaMiles). The aim of this research is to analyze the influence of service quality toward sales of ticket and membership of Garuda Indonesia. The analysis method that used in this research is Time Series Regression. Tangible, reliability, responsiveness, assurance and empathy are the independent variables of this research. While, dependent variables of this research are sales of ticket and membership. The population of this research is airplane in Indonesia and the sample of this research is Garuda Indonesia Airline. The result of this research shows that based on F test, all independent variables (tangible, reliability, responsiveness, assurance and empathy) have simultaneous influence on sales of ticket and all independent variables (tangible, reliability, responsiveness, assurance and empathy) also have simultaneous influence on membership. While, based on T test not all independent variables in this research influence sales of ticket of Garuda Indonesia partially. The independent variable that influences sales of ticket partially is tangible and independent variables that partially influence membership are tangible, responsiveness and empathy.